Respuesta :

Dehan

Step-by-step explanation:

All u have to is subject t from that formula.

D=C( 1 + rt/100)

D/C = 1+ rt/100

D/C - 1 = rt/100

So,

When u multiply the equation by 100 and divide by r it will be as follows.

(D/C -1)100/r = t

It is the answer C.

And now to get the answer E,

we have the equation as t = (D/C-1) 100/r

First solve what inside the bracket.

D/C - 1

D/C - C/C

(D-C)/C

So when u put that to the above,

t= (D-C/C) 100/r

Now all u have to do is just multiply

t= 100(D-C) / Cr

ACCESS MORE